Cognitive Construction of Pandemic: A Corpus-based Study of Conceptual Metaphors of Covid-19 in Pakistani English Newspapers - Umer, Shukraan bin; Malik, Moazzam Ali; Manzoor, Humayun (Annals of Human and Social Sciences, 2022)
Conceptual metaphors are quite common in our everyday discourses. They are used to express abstract and complex concepts in term of concrete entities. Conceptual metaphors help us understanding how language and cognition intersect to frame our understanding of the abstract concepts. COVID-19, in recent times, has severely affected the world has caused millions of deaths. The study explores how “Covid-19, Corona, and Coronavirus” terms are used for source domain mappings and metaphorical representations in Pakistani English newspapers. For this purpose, the data was collected from the sub-corpus “Coronavirus Corpus” of a web-based Corpus “English-Corpora” (https://www.english-corpora.org/). The researcher applies a modified version of the metaphor Identification Procedure (MIP), originally proposed by Group (2007), on the collected corpus data. The findings of the study indicate that, in Pakistani newspaper discourse, Covid-19 is mapped onto different source domains like, animal, threat, enemy, tsunami, etc.